TEACHERS’ QUALITY AND GENDER AS PREDICTORS OF PRIMARY SCHOOL PUPILS’ ACADEMIC PERFORMANCE IN ANAMBRA STATE - Okika, Chinyere Love; David, Perpetua Adaora (Journal of Early Childhood and Primary Education, 2025)
This Study investigated teacher quality and gender as predictors of primary school pupils’ academic performance in Anambra State. Five research questions and five null hypotheses guided the study. Correlational research design was employed for the study. A sample of three hundred and sixty (360) primary school teachers out of a population of 11,971 was used. Multi stage sampling procedure was used to draw the sample. The instruments for data collection were the Teacher Quality and Gender questionnaire (TQGQ) and academic performance scale. The instrument was validated by two experts in the Department of Early Childhood and Primary Education, and one expert from the Department of Educational Foundations (Measurement and Evaluation), Faculty of Education, Nnamdi Azikiwe University, Awka. Cronbach Alpha statistics was used to compute reliability coefficient which yielded a coefficient of 0.88 for the teachers’ verbal ability and 0.65 for teachers’ use of instructional skills. The research questions and the hypotheses were analyzed using regression analysis, Findings revealed that teachers’ qualification predicted primary school pupils’ academic performance in Anambra state to a weak degree, teachers’ verbal ability predicted primary school pupils’ academic performance in Anambra state to a modest degree, teachers’ use of instructional skills predicted primary school pupils’ academic performance in Anambra state to a modest degree, teachers’ gender predicts primary school pupils’ academic performance in Anambra state to a weak degree and teachers’ quality (qualification, verbal ability, use of instructional skills) and gender jointly predicted primary school pupils’ academic performance in Anambra State to a modest degree. Based on the findings, it was recommended that teacher education institutions should place stronger emphasis on practical training that develops verbal communication skills and mastery of instructional strategies alongside theoretical knowledge. Ministries of Education and school administrators should organize regular capacity-building workshops and seminars focused on effective communication and instructional practices for primary school teachers and that recruitment and promotion of teachers should not be based solely on academic qualifications but should incorporate evaluation of teaching competence, classroom performance, and communication ability among others.
Keywords: Teacher Quality; gender; academic performance; verbal ability; instructional skill; teacher qualification